A Theoretical Study of Scattering of Electrons and Positrons by CO2 Molecule - M. Masum Billah; M. Mousumi Khatun; M. M. Haque; M. Yousuf Ali; Mahmudul H. Khandker; A. K. F. Haque; Hiroshi Watabe; M. Alfaz Uddin (Atoms, 2022)
This article presents a theoretical investigation of the differential, integrated, elastic, inelastic, total, momentum-transfer, and viscosity cross-sections, along with the total ionization cross-section, for elastically scattered electrons and positrons from a carbon dioxide (CO<semantics>2</semantics>) molecule in the incident energy range of 1 eV <semantics>≤Ei≤</semantics> 1 MeV. In addition, for the first time, we report the spin polarization of e<semantics>±−</semantics>CO<semantics>2</semantics> scattering systems. The independent atom model (IAM) with screening correction (IAMS) using a complex optical potential was employed to solve the Dirac relativistic equation in partial-wave analysis. The comparison of our results with the available experimental data and other theoretical predictions shows a reasonable agreement in the intermediate- and high-energy regions.